Challenges of antimicrobial resistance in sub-Saharan Africa: The past, present, and future perspectives - Elijah, O. B.; Umukoro, E. K.; Moke, E. G.; Igben, V. J. O.; Arighwrode, O.; Onakpoya, E. E.; Dennis-Eboh, U.; Ekuerhare, B. E. (Orapuh Journal, 2024)
Infectious diseases continue to be a major global problem in public health, accounting for millions of fatalities annually, despite a century of frequently successful preventative and control efforts. Antimicrobial resistance (AMR) and the appearance of novel diseases are both consequences of the rapid pace at which society, technology, and microbes are changing. It is projected that AMR was responsible for the deaths of 700,000 people around the world in 2014, making it one of the most significant threats to the world’s public health. This essay points to the challenges of antimicrobial resistance in sub-Saharan Africa and its prospects. An online search was done on relevant published studies in PubMed, Scopus, Embase, and ResearchGate from the period 1992 to 2023, of which 61 were adapted for this article. The sub-Saharan Africa region, despite being the worst hit when it comes to infectious disease and, by proxy, antimicrobial resistance, can win the war in the long run.